924 The Effect of COVID On the Skin Cancer Referral Pathway. (4th May 2021) - Ali, S; Dunne, J
Abstract: Introduction: Due to COVID resulting in all elective surgeries being cancelled; it was thought that patients with suspected skin cancer maybe seeing a specialist and having surgery later than. So, to tackle this as lockdown occurred, the Plastic Surgery department at Charing Cross Hospital secured a minor operation room in outpatients, to keep treating suspected skin cancer. But did it work? Method: Data was collected from an interval of 2 months before the pandemic (December-January) and 2 months post the pandemic (April-May). Each suspected skin cancer patient who was put on the two weeks wait referral during that time had their receipt of referral, first appointment with a specialist and date of surgery (if that was done) recorded. Results: Before COVID 81% of patients were seen by a specialist in 2 weeks compared to 89% after COVID. Also, 78% of patients had achieved surgery within 62 days before the pandemic, compared to 86% after the pandemic. Conclusions: In conclusion, the results showed that the implementation of the minor operation room at short notice enabled the department to meet capacity. Thus, it is utilisation going forward can improve how quickly skin cancers are managed.